2019
DOI: 10.1109/jstqe.2019.2937445
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Chaotic and Spiking Dynamics in Mid-Infrared Quantum Cascade Lasers Operating Continuous-Waves and Under Current Modulation

Abstract: This study investigates chaotic and spiking dynamics of mid-infrared quantum cascade lasers operating under external optical feedback and emitting at 5.5 µm and 9 µm. In order to deepen the understanding, the route to chaos is experimentally studied in the case of continuous-wave and current modulation operation. The non-linear dynamics are analyzed with bifurcation diagrams. While for quasi-continuous wave operation, chaos is found to be more complex, pure continuous wave pumping always leads to the generatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…4,18 In our case, when the QCL is pumped with a quasi-continuous wave (QCW), the best results are obtained in term of chaos complexity. 19 However, this configuration may not always be suitable because it can be difficult to include the message to be transmitted while the laser is already pumped with a QCW. Furthermore, the transmission tentative can become easier to detect for an eavesdropper, thus destroying the benefit of the stealth.…”
Section: Description Of the Apparatusmentioning
confidence: 99%
See 1 more Smart Citation
“…4,18 In our case, when the QCL is pumped with a quasi-continuous wave (QCW), the best results are obtained in term of chaos complexity. 19 However, this configuration may not always be suitable because it can be difficult to include the message to be transmitted while the laser is already pumped with a QCW. Furthermore, the transmission tentative can become easier to detect for an eavesdropper, thus destroying the benefit of the stealth.…”
Section: Description Of the Apparatusmentioning
confidence: 99%
“…On the other hand, pure continuous wave pumping leads to a more regular spiking dynamics that can be controlled by adding current modulation. 19 This entrainment phenomenon studied by adding sine and square wave modulations allows finely triggering the spiking that is suitable for secure communications where the chaos itself contains the secret message. 33 Moreover, developed chaos can also be found in this configuration for narrow ranges of feedback ratios.…”
Section: Towards Mid Infrared Private Communicationsmentioning
confidence: 99%
“…As for free-space communication, only numerical modeling has proven the possibility of a private free-space communication, but for laser diodes in the near-infrared 38 . Our prior works showed that QCLs are, under certain conditions, able to exhibit mid-infrared chaotic oscillations 39 , 40 .…”
Section: Introductionmentioning
confidence: 99%
“…These studies complimented findings showing the high transmission potential of midinfrared devices in the two transparency windows of the atmosphere, namely 3-5 µm and 8-12 µm. When subjected to external optical feedback, QCLs are known to be more resistant than other semiconductor lasers [4] but still exhibit several non-linear dynamics [5]. Amid these phenomena, excitability can be detrimental for communications because it blurs the encoded signal.…”
Section: Introductionmentioning
confidence: 99%